“De fato, eles punham os deveres para com os deuses acima dos deveres para com os homens": paisagem religiosa na Esparta do Arcaico ao Helenístico - Silva, Cleyton Tavares da Silveira (2023)
This thesis aims to understand through which processes and actions the construction, development and maintenance of a Religious Landscape in Sparta, between the 8th and 3rd centuries BC, was viable, with religious language as an intermediary action, essential to the composition of the polis, through their rites, rituals, processions and cults. This operation sought to establish social cohesion through a Religious Identity among the inhabitants of Laconia, mainly those who resided in the Plain of Sparta, where they were arranged as ôbai, as villages forming the polis. To do so, we will make use of the observation of available literary records, such as Herodotus, Thucydides, Xenophon, Plutarch and Pausanias. Likewise, this research focuses on the cultural material coming from the destroyed sites excavated at the site of ancient Sparta, essentially, the remains of the sanctuaries arranged around the Spartan obais, seeking to trace in these documents traces, characteristics that demarcated the singularities of the ancient inhabitants of Sparta. To carry out such an undertaking, this thesis analyzes a broader general framework, linked to the complexion of Spartan religiosity, its festivals and cults, the sanctuaries of Artemis Orthia, Athena Chalkíoikos, Menelaion and Amiclaion.